SURGICAL GINGIVECTOMY AND GINGIVOPLASTY ON UPPER ANTERIOR TOOTH - Sukmawati, Ayuda Nur; Ramadhani, Aulia Puspasari; Dewi, Hidha Rahma Sintya (Indonesian Journal of Dentistry, 2025)
ABSTRACTBackground: Gingival enlargement can be treated with periodontal therapy, starting with the initial phase therapy, which includes dental health education and scaling-root planing. When the enlargement persists after the initial treatment is carried out, a surgical procedure, namely gingivectomy, is needed.Method: A 22-year-old male patient came to RSGM UNIMUS complaining that his upper front gums appeared enlarged. The patient had been aware of the complaint since the examination during the scaling procedure two weeks ago. There was no pain in the enlarged gums, but they bled when brushing his teeth. The patient wanted to get treatment for his gums. The patient denied any relevant medical history and allergies.Outcome: The gingivectomy in this patient improved the gingiva appearance and lengthened the clinical crown on the upper anterior teeth.Conclusion: Gingivectomy was proven to be an effective surgical therapy to eliminate gingival enlargement and maintain the proportional gingival appearance, especially on the anterior teeth. However, considering the complexity of the case, more extensive mouth rehabilitation is required.